2017
DOI: 10.1007/s12410-017-9400-x
|View full text |Cite|
|
Sign up to set email alerts
|

Novel Noninvasive Nuclear Medicine Imaging Techniques for Cardiac Inflammation

Abstract: Purpose of ReviewInflammation is a key player in a wide range of cardiovascular and myocardial diseases. Given the numerous implications of inflammatory processes in disease initiation and progression, functional imaging modalities including positron emission tomography (PET) represent valuable diagnostic, prognostic, and monitoring tools in patient management. Since increased glucose metabolism is a hallmark of inflammation, PET using the radiolabeled glucose analog [18F]-2-deoxy-2-fluoro-d-glucose (FDG) is t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 135 publications
0
17
0
2
Order By: Relevance
“…As inflammation has been widely established as increasing cardiovascular disease risk [2426], our finding at least partially explains the pathway of autonomic neuropathy for increasing such risk. More research needs to be performed to validate our result.…”
Section: Discussionmentioning
confidence: 57%
“…As inflammation has been widely established as increasing cardiovascular disease risk [2426], our finding at least partially explains the pathway of autonomic neuropathy for increasing such risk. More research needs to be performed to validate our result.…”
Section: Discussionmentioning
confidence: 57%
“…Another possible reason for the low specificity observed in other studies is that myocardial ischemia and heart failure may also produce focally or heterogeneously increased 18 F-FDG uptake not related to sarcoidosis. 18 F-FDG PET may also visualize acute myocardial inflammation to suggest active myocarditis [ 38 ]. A meta-analysis for pulmonary lesion diagnosis reported that 18 F-FLT showed better results compared with 18 F-FDG in ruling out inflammation-based lesions [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has proven its value in inflammatory conditions such as myocarditis, endocarditis, sarcoidosis, pericarditis, amyloidosis, and implantable electronic device infections. [ 39 ] In suspicion of endocarditis on a prosthetic valve, abnormal activity around the site of implantation detected by18F-FDG PET/CT (If prosthesis was implanted for >3 months) or radiolabeled leucocyte SPECT/CT is considered a major criterion in recent guideline. [ 40 ]…”
Section: Interpretation In the Heart And Vascular Diseasementioning
confidence: 99%